Electric vehicle charging strategy to support renewable energy sources in Europe 2050 low-carbon scenario. (15th September 2019) - Colmenar-Santos, Antonio; Muñoz-Gómez, Antonio-Miguel; Rosales-Asensio, Enrique; López-Rey, África
Abstract: The EU has undertaken a thorough reform of its energy model. Current EU 2050 climate commitment sets an 80–95% GHG reduction goal. To reach this goal, the EU must make continued progress towards a low-carbon society. Renewable energy sources and electric vehicle play an important role for a gradual transition. The power grid faces a challenging future due to intermittency and the non-dispatchable nature of wind and solar energy production, but flexibility needs can migrate from generation to load, with the expansion of demand-side resources and storage technologies. A novel grid technique is presented and evaluated in this paper for the optimal integrated operation of renewable resources and electric vehicle to increase penetration of renewable energy. It is proposed a distribute control system to manage a charge and discharge strategy to support mismatching between load and renewable generation thru V2G technology. Demand response, peak saving and ancillary services are introduced to keep a reliable power quality, stable frequency and flatten load profile. Graphical abstract: Image 1 Highlights: Europe 2050 low-carbon scenario based on RES and energy efficiency is reviewed. The effects of high renewable and efficient electricity system are assessed. A smart charging strategy for EV is presented to provide grid services. Demand response and EV storage are analyzed to match with non-dispatchable resources. The impact of proposed charging strategy on electric load curve is evaluated.